Treatment of active lupus nephritis with the novel immunosuppressant 15-deoxyspergualin: an open-label dose escalation study - Lorenz, Hanns-Martin; Schmitt, Wilhelm; Tesar, Vladimir; Müller-Ladner, Ulf; Tarner, Ingo; Hauser, Ingeborg A.; Hiepe, Falk; Alexander, Tobias; Woehling, Heike; Nemoto, Kyuichi; Heinzel, Peter A. (Arthritis Research & Therapy, 2011)
As the immunosuppressive potency of 15-deoxyspergualin (DSG) has been shown in the therapy of renal transplant rejection and Wegener's granulomatosis, the intention of this study was to evaluate the safety of DSG in the therapy of lupus nephritis (LN). Patients with histologically proven active LN after prior treatment with at least one immunosuppressant were treated with 0.5 mg/kg normal body weight/day DSG, injected subcutaneously for 14 days, followed by a break of one week. These cycles were repeated to a maximum of nine times. Doses of oral corticosteroids were gradually reduced to 7.5 mg/day or lower by cycle 4. Response was measured according to a predefined decision pattern. The dose of DSG was adjusted depending on the efficacy and side effects. A total of 21 patients were included in this phase-I/II study. After the first DSG injection, one patient was excluded from the study due to renal failure. Five patients dropped out due to adverse events or serious adverse events including fever, leukopenia, oral candidiasis, herpes zoster or pneumonia. Eleven out of 20 patients achieved partial (4) or complete responses (7), 8 were judged as treatment failures and 1 patient was not assessable. Twelve patients completed all nine cycles; in those patients, proteinuria decreased from 5.88 g/day to 3.37 g/day (P = 0.028), Selena-SLEDAI (Safety of Estrogens in Lupus Erythematosus - National Assessment - systemic lupus erythematosus disease activity index) decreased from 17.6 to 11.7. In 13 out of 20 patients, proteinuria decreased by at least 50%; in 7 patients to less than 1 g/day. Although the number of patients was small, we could demonstrate that DSG provides a tolerably safe treatment for LN. The improvement in proteinuria encourages larger controlled trials. ClinicalTrials.gov: NCT00709722